Local Allergic Rhinitis in Children: Novel Diagnostic Features and Potential Biomarkers. Issue 5 (September 2016) - Zicari, Anna Maria; Occasi, Francesca; Di Fraia, Marco; Mainiero, Fabrizio; Porzia, Alessandra; Galandrini, Ricciarda; Giuffrida, Anna; Bosco, Daniela; Bertin, Serena; Duse, Marzia
Background: Local allergic rhinitis (LAR) is a phenotype of rhinitis that has been poorly studied in children. It is characterized by the same symptoms of allergic rhinitis but with the absence of markers of systemic atopy. Objective: To identify children affected by LAR and to analyze the pathogenesis of this disease. We chose to focus our attention on interleukin (IL) and thymic stromal lymphopoietin (TSLP). Methods: We enrolled 20 children affected by nonallergic rhinitis (negative skin-prick test results and serum specific immunoglobulin E [sIgE] values). Each patient underwent a nasal allergen provocation test (NAPT) with dust mite and grass pollen. Before and after NAPT, nasal lavage was performed to detect sIgE, IL-5, and TSLP; anterior active rhinomanometry was used to evaluate changes in nasal obstruction. Results: Two patients were positive to a nonspecific NAPT and, thus, were excluded from the study. Of the remaining 18 children, 12 (66.7%) had positive results to at least one NAPT. Among these 12 patients, nasal sIgE levels for Dermatophagoides pteronyssinus, Dermatophagoides farinae, and Lolium perenne increased significantly after NAPT (D. pteronyssinus, p < 0.005 ; D. farinae, p < 0.05 ; L. perenne, p < 0.05). Nasal IL-5 levels showed a significant increase after NAPT (p ≤ 0.006), and this increase was significantly higher in children who had positive NAPT results than in those patients with negative NAPT results (p ≤ 0.03). Among the 12 children who had a positive NAPT result, nasal TSLP was detected in 4 patients (33.3%) and its levels showed a relevant increase after NAPT, even though the difference did not reach statistical significance (p ≤ 0.061). Conclusion: Observed results raise the importance of better refining the diagnostic protocol for LAR in children. Nasal TSLP and IL-5 levels offer new insights concerning localized allergic inflammation, although the role of nasal sIgE has still to be clarified.